2015
DOI: 10.1111/ppa.12408
|View full text |Cite
|
Sign up to set email alerts
|

Is the onset of septoria tritici blotch epidemics related to the local pool of ascospores?

Abstract: To elucidate the early epidemic stages of septoria tritici blotch, especially the relationship between the onset of epidemics, the local availability of primary inoculum, and the presence of wheat debris, the early disease dynamics and airborne concentration in Zymoseptoria tritici ascospores were concomitantly assessed at a small spatiotemporal scale and over two years, using spore traps coupled with a qPCR assay. One plot, with the crop debris left, provided a local source of primary inoculum, while the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Fifteen isolates representative of the initial population (Pi) was sampled by destructive harvesting (five plants randomly collected in five 1-m 2 quadrats per plot, located 20 m away from each other) at the beginning of the epidemic, in late autumn (from 24 November to 8 December 2009), from the first 15 lesions detected on the first leaves of seedlings. The first contaminations probably occurred in late October as soon as the first wheat leaves emerged and originated exclusively from wind-dispersed ascospores of distant origin, because no wheat residues were present in the field (23,24). Fifteen isolates representative of the final population (Pf) was sampled at the end of the epidemic, in early summer (12 July 2010), from the first 15 lesions found on either the antepenultimate (F3) or penultimate (F2) leaf of the main tiller.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen isolates representative of the initial population (Pi) was sampled by destructive harvesting (five plants randomly collected in five 1-m 2 quadrats per plot, located 20 m away from each other) at the beginning of the epidemic, in late autumn (from 24 November to 8 December 2009), from the first 15 lesions detected on the first leaves of seedlings. The first contaminations probably occurred in late October as soon as the first wheat leaves emerged and originated exclusively from wind-dispersed ascospores of distant origin, because no wheat residues were present in the field (23,24). Fifteen isolates representative of the final population (Pf) was sampled at the end of the epidemic, in early summer (12 July 2010), from the first 15 lesions found on either the antepenultimate (F3) or penultimate (F2) leaf of the main tiller.…”
Section: Methodsmentioning
confidence: 99%
“…It was decided to assess the trapping frequencies, because it is an appropriate measurement for the analysis of the spatial distribution of spore depositions within stands (Garbelotto et al, 2007). Moreover, previous experience using paper filter spore traps has shown that qPCR Ct values can be below the detection limit of the assays (Aguayo et al, 2018;Fourie et al, 2014), which means that the pathogen is present in the samples, but not at quantifiable concentrations (Grosdidier et al, 2017;Morais, Sache, Suffert, & Laval, 2016). In these cases, it is better to class these samples into a "detectable but not quantifiable class," as suggested by Morais et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous experience using paper filter spore traps has shown that qPCR Ct values can be below the detection limit of the assays (Aguayo et al, 2018;Fourie et al, 2014), which means that the pathogen is present in the samples, but not at quantifiable concentrations (Grosdidier et al, 2017;Morais, Sache, Suffert, & Laval, 2016). In these cases, it is better to class these samples into a "detectable but not quantifiable class," as suggested by Morais et al (2016). In our study, if one of the spore traps or one batch of insects was positive, the trap by location was considered positive.…”
Section: Discussionmentioning
confidence: 99%
“…Within necrotic lesions, the fungus begins to reproduce asexually and later sexually (Eyal et al 1987;Eyal 1999;Ponomarenko et al, 2011). Airborne ascospores typically constitute the primary inoculum released from wheat debris (Suffert & Sache, 2011;Morais et al, 2016). Pycnidiospores are splash-dispersed and are transmitted more locally infecting nearby plants.…”
Section: Introductionmentioning
confidence: 99%